Caracterização de meios filtrantes através do estudo das normas de padronização de testes europeia e americana - Lista, Ana Elisa (2018)
Nowadays, people spend considerable part of their time indoors with air conditioners on. Even at work, in a car or at home, they expose themselves to what is known as indoor air pollution. The market offers a variety of filters with different efficiency performances, thus serving for different applications. In order to know which one is most appropriate to a given situation, standards should be used that describe filter ratings, which are performed through standardized tests. However, such standards provide different information regarding efficiency, dust holding capacity and load loss. Consequently, the lack of correlation between them causes doubts and misuse of the filters. Against this background, the main objective of this study is to carry out experiments following the tests of European standards (EN 779/1822) and also American (ASHRAE 52.2) in order to compare them later. Five different filter media were used. They are divided into two categories: HEPA filters (glass and quartz) and industrial filters (celulose, activated carbono and polyester).In order to simulate the passage of air through the filter, an experimental apparatus was adapted, taking into account the specific restrictions of each standardization. First, the characterization of the filters (fiber diameter, porosity and thickness) were carried out by means of the Scanning Electron Microscope (SEM). Afterwards, efficiency following each standardization condition (different aerosol) was collected. The HEPA filters results when compared are very similar (close to 100%). However, only American standard was able to give a better ranking for the filter media of quartz. Between the coarse filters, American and European showed that cellulose is more efficient. The same filter has shown different efficiency values depending on the standard condition which was chosen.